Implementation Of Nusantara Musicals Ideas In The Song Of Yadapati Tiwikrama By Djiwoastra (Jurnal Seni Musik, 2022)
Djiwoastra is a folk metal band from Surakarta that has succeeded in combining two genres of music, namely metal and tradisional indonesian music. The song Yadapati Tiwikrama contains the idiomatic indonesian archipelago, taking the theme of the history of the maritime wars in 7th century. This research was qualitative with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicated that there was aplication of ideas that contain idiomatic archipelagoes through musical compositions and concepts in the song Yadapati Tiwikrama in the form of : 1) Interpretation of the superiority of the Javanese maritime troops in the invasion of the Po Nagar in the 7th century through motifs, intervals, and textures on musical compositions, 2) there are cultural elements contained in the song, such as : a) traditional art elements in the form of Balinese Bale Ganjur Bali Instrument, b) language elements by the pronunciation of Balinese incantation that adopt the idea of suluk Sidakarya, c) religious elements by the concept of the religion system of the God of the ocean.